A research annual - Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2004)
Contains four sets of refereed essays. One group includes papers on Harrod and Robertson; Adam Smith; Keynes; Mendeleev; Veblen; and J. M. Clark. The second group has six papers on the historiography of institutional economics during the inter-war period. The third group has two papers on a conference on the status of the status quo. The fourth group has thirteen essays each reviewing one or more recent works.